Understanding leader evaluations in European Parliament elections. (March 2022) - Gattermann, Katjana; de Vreese, Claes H.
Leader evaluations are a crucial aspect in representative democracy. We analyse the patterns, antecedents and consequences of European Union leader evaluations against the backdrop of the 2019 European Parliament elections in ten countries. The article shows, firstly, that leader evaluations are unidimensional, both among voters with low and high knowledge as well as partisans and non-partisans. Secondly, among the antecedents of leader evaluations, European Union trust and performance evaluations are positively associated with leader evaluations, while European identity hardly plays a role compared to other factors. Lastly, the positive effect of leader evaluations on vote choice is conditional upon the individual leader and their party affiliation. Our results have important implications for expectations towards and evaluations of European Union leadership in the long term.